Cryptic dispersal networks shape biodiversity in an invaded landscape. Issue 8 (3rd June 2019) - Germain, Rachel M.; Jones, Natalie T.; Grainger, Tess Nahanni
Abstract: Species interact with the physical world in complex ways, and life‐history strategies could cause species to differ in how they experience the connectedness of the same landscape. As a consequence, dispersal limitation might be present but not captured by distance‐based measures of connectivity. To test these ideas, we surveyed plant communities that live on discrete patches of serpentine habitat embedded within an invaded nonserpentine habitat matrix. Species in these communities differ in dispersal mode (gravity, animal, or wind); thus we used satellite imagery to quantify landscape features that might differentially influence connectivity for some dispersal‐ mode groups over others (surface streams, animal paths). Our data yielded two key insights: first, dispersal limitation appeared to be absent using a conventional distance‐based measure of connectivity, but emerged after considering forms of landscape connectivity relevant to each dispersal mode. Second, the landscape variables that emerged as most important to each dispersal mode were generally consistent with our predictions based on species' putative dispersal vectors, but also included unexpected interactive effects. For example, the richness of animal‐dispersed species was positively associated with animal connectivity when patches were close in space, but when patches were isolated, animals had a strong negative effect. This finding alludes to the reduced ability of animals to disperse seeds between suitable patches in invaded landscapes because of increased inter‐patch distances. Real landscapes include complex spatial flows of energy and matter, which, as our work demonstrates, sets up ecological opportunity for organisms to differ in how they disperse in a common landscape.